2022
DOI: 10.3390/ani12223116
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Mapping and Biopsy in Cats with Solid Malignancies: An Explorative Study

Abstract: There is increasing evidence on the utility of sentinel lymph node (SLN) biopsy (SLNB) for the staging of dogs with various malignancies; however, comparable information is missing in cats. This multi-institutional study aims at reporting the feasibility and detection rate of SLNB guided by lymphoscintigraphy and the blue dye or near-infrared fluorescent lymphography (NIRF-L) in cats with solid tumors. In total, 12 cats presented with 14 solid malignancies that underwent curative-intent surgical excision of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…SLNs may be the regional LNs anticipated to be responsible for tumor drainage; however, the LNs at unpredictable anatomical locations might also serve as SLNs [20]. Indeed, for dogs, regional LNs do not correspond to SLNs in 42-63% of cases [10,20,24,25], and a recent study in cats found an even higher discrepancy (71.4%) [26].…”
Section: Sln Mapping In Companion Animalsmentioning
confidence: 98%
See 3 more Smart Citations
“…SLNs may be the regional LNs anticipated to be responsible for tumor drainage; however, the LNs at unpredictable anatomical locations might also serve as SLNs [20]. Indeed, for dogs, regional LNs do not correspond to SLNs in 42-63% of cases [10,20,24,25], and a recent study in cats found an even higher discrepancy (71.4%) [26].…”
Section: Sln Mapping In Companion Animalsmentioning
confidence: 98%
“…The same group also published a study evaluating lymphoscintigraphy in head and neck tumors, for which a lower detection rate of 83% was observed [13]. Finally, a recent study revealed the successful usage of lymphoscintigraphy for the detection of SLN in cats with various solid tumors [26].…”
Section: Lymphoscintigraphymentioning
confidence: 99%
See 2 more Smart Citations
“…Indocyanine green also has an excellent safety profile and has been demonstrated to have no significant side effects in companion animals ( 49 ). Applications have included SLN mapping of the oral, head and neck region, caudal abdomen and limbs in healthy and diseased dogs and head and neck region, trunk, perineum, and limbs in healthy and diseased cats ( Figure 3 ) ( 22 , 29 , 41 , 46 , 47 , 50 ). As a result, this technique is gaining popularity in the veterinary field; however, limitations include the accessibility of NIRF equipment and a lack of protocol standardization.…”
Section: Sentinel Lymph Node Mapping Techniques In Veterinary Medicinementioning
confidence: 99%